(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2021)
Our country boasts the pride of having been the cradle of university institutions. Today, however, Italy, among the great countries of the West, is the one that attracts fewer foreign students in relation to the size and historical quality of its system. university. One of the causes of this weakness (apart from some, but a few exceptions) is certainly the inadequacy - in terms of quantity and quality - of the supply of modern university residences and colleges The Studanteum is an Academic Center of residence and study of Sapienza, to be built in every city in the world. In it will be present the memory of the work of Dante, our great poet, both by drawing a Lampa in steel and light from the image of the circles of the blessed around the supreme wisdom, and by basing the new project on the dynamic use of the golden spiral that Giuseppe Terragni used in his famous Danteum. The spiral will shape the volumes of the study, entertainment and recreation spaces, crowned by the ‘Lampa della Sapienza’. The project is scalable, that is, it can be adapted to different urban lots.